2019
DOI: 10.1002/star.201800272
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Swelling Behavior of Super-Absorbent Soluble Starch-g -poly(AM-co -NaAMC14 S) Through Graft Copolymerization and Hydrolysis

Abstract: By introducing sodium 2‐acrylamido‐tetradecanesulfonate (NaAMC14S) to graft copolymerization of soluble starch and acrylamide (AM), a novel super absorbent resin (SAR) of soluble starch‐g‐poly(AM‐co‐NaAMC14S) (SR‐14) is synthesized. Polymer gels are hydrolyzed with sodium hydroxide (NaOH) to convert the function group −CONH2 to −COO‐. The structures and qualitative changes of the polymer gels are characterized through Fourier transform infrared spectroscopy (FT‐IR), scanning electron microscopy (SEM), elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The FT-IR spectra of the ST, SA, SAP, SAPC and KL are shown in Figure 1. The FT-IR spectrum of ST is shown in Figure 1a, peaks at 1158, 1081 and 1005 cm −1 were the stretching vibration of the C-O-C bond [30,31]. After polymerization, these peaks shifted and weakened.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…The FT-IR spectra of the ST, SA, SAP, SAPC and KL are shown in Figure 1. The FT-IR spectrum of ST is shown in Figure 1a, peaks at 1158, 1081 and 1005 cm −1 were the stretching vibration of the C-O-C bond [30,31]. After polymerization, these peaks shifted and weakened.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…For swollen hydrogel systems, according to the relative diffusion rate of water into the polymer matrix and the relaxation of the polymer chain, the diffusion mechanism of water molecules can be divided into ve types: (1) n < 0.5, pseudo-ckian diffusion; (2) n = 0.5, Fickian diffusion; (3) 0.5 < n < 1, non-ckian diffusion; (4) n = 1, Case II transmission diffusion; (5) n > 1, relaxation diffusion [49]. The equation is suitable for the initial stage of swelling process [35].…”
Section: Swelling Kineticsmentioning
confidence: 99%
“…The water absorbency of CMS-g-poly (AA-co-AM) resin with different crosslinking degrees in the deionized water was determined, and the method was referred to a literature (Lan et al 2019). Moreover, the heavy metal adsorption ca-pacity and mechanisms of the optimized resin product were observed in four solutions, including CrCl3, CuSO4, NiCl2, and ZnSO4 with a concentration of 200 mg/L.…”
Section: Water Absorbency and Heavy Metal Adsorption Measurementmentioning
confidence: 99%
“…In addition, the adsorbents are partially similar with a new functional polymer with highly insolubility character, called super absorbent resin (SAR), which have numerous hydrophilic groups, such as -COO − and -OH, and can conserve water at hundreds or even thousands of its weight. Meanwhile, in our previous research to obtain SAR by soluble starch and acrylamide under the graft copolymerization and hydrolysis reaction, we found that the water absor-bency of SAR was inversely related with the crosslinker concentration and the increase of the crosslinker concentration resulted in the decrease of water absorbency (Lan et al 2019). Based on the observation, we put forward a hypothesis that increasing the crosslinker content enormously can greatly hinder the water-absorbing expansibility of SAR, which might be conducive to material transfer process and make polymer falls back on excellent heavy metal adsorption capacity.…”
Section: Introductionmentioning
confidence: 98%